Postural assessment of girls between 7 and 10 years of age Avaliação postural em meninas de 7 a 10 anos - Patrícia Jundi Penha; Sílvia Maria Amado João; Raquel Aparecida Casarotto; Carlos Junichiro Amino; Daniela Caielli Penteado (Clinics, 2005)
Postural alterations are often found in children and teenagers. In this stage of development, the posture undergoes many adjustments and adaptations due to changes of the body and to demanding psychosocial factors. PURPOSE: To identify which postural alterations occur most often in students between 7 and 10 years of age, to identify preventive measures, and to provide information to parents and teachers about the problem of bad posture. METHODS: Thirty three girls in each of 4 age groups between 7 and 10 years of age were assessed, resulting in a sample of 132 subjects. Photos of each girl in the sagittal and frontal planes were examined for postural deviations. RESULTS: The main postural deviations found were knock-knee, medial rotation of the hip, antepulsion, pelvic anteversion, knee hyperextension, lumbar hyperlordosis, valgus ankle, imbalanced shoulders, lateral pelvic inclination, scoliosis, trunk rotation, thoracic hyperkyphosis, winged scapula, shoulder protraction, abducted scapula, medial rotation of shoulders, and head tilt. CONCLUSION: High incidences of postural alterations occur in children of school age. Some of these reflect normal postural development, and get corrected during the child's growth. On the other hand, some alterations are asymmetries that can be caused by daily demands on the body and can result in negative impacts on the quality of life during childhood and adulthood. We emphasize the importance of providing information to parents and teachers about the problem of bad posture. Alterações posturais são freqüentemente encontradas em crianças e adolescentes. Nessa fase, a postura sofre uma série de ajustes e adaptações às mudanças no próprio corpo e à demanda psicossocial que lhe é apresentada, ocorrendo uma grande transformação na busca de um equilíbrio compatível com suas condições. OBJETIVO: Identificar quais as alterações posturais mais freqüentes em escolares, de 7 a 10 anos, com intuito de fundamentar medidas preventivas e, secundariamente, alertar pais e professores para o problema da má postura. MÉTODOS: Foram avaliadas 33 meninas para cada idade entre 7 a 10 anos, totalizando uma amostra de 132 sujeitos. Cada estudante foi observado através de fotos nos planos frontal e sagital. RESULTADOS: Os principais desvios posturais encontrados foram: joelho valgo, rotação medial de quadril, antepulsão, anteversão pélvica, hiperextensão de joelho, hiperlordose lombar, tornozelo valgo, desnível de ombro, inclinação pélvica lateral, escoliose, rotação de tronco, hipercifose torácica, escápula alada, protração de ombros, abdução escapular, rotação medial de ombro e inclinação de cabeça. CONCLUSÃO: Este estudo alcançou seu objetivo de descrever os padrões posturais mais freqüentes entre meninas de 07 a 10 anos. Algumas das alterações posturais descritas são próprias do desenvolvimento postural normal da criança e tendem a serem incorporadas com seu crescimento - como o valgismo de joelho, a rotação medial de quadril e a hiperlordose lombar. Outras, no entanto, caracterizam assimetrias que podem ser geradas por demandas diárias como, por exemplo, a escoliose.